Mining extractivism in Bogotá: contributions to the debate from the perspective of urban environmental history (2022)
The present article aims to understand the socio-environmental conflicts caused by mining extractivism in the city of Bogotá. For this purpose, three sections are proposed: the first deals with some conceptual and methodological understandings presented by the author on urban environmental history (UAH), which allows the problematization and complexification of socially constructed territories, setting up a counterpoint with some references of urban geography. The second section analyses the mining heritage from three historical periods of the UAH of Bogotá: 1) the colonial period and pottery; 2) the modernization of the city and the mining areas; 3) urban growth and the presence of mining-industrial parks (MIP), placing special emphasis on the MIP in the south of the city from the perspective of extractivism to proceed to analyze the economic dynamics behind mining and its environmental effects. The third section presents the conclusions.